Consumption Expenditures in Austria & Germany: New Evidence Based on Transactional Data - Winfried Koeniger; Peter Kress; Jonas Lehmann (Institute of Labor Economics (IZA), 2024)
We analyze the novel transactional card expenditure data for Germany and Austria provided by Fable Data. We describe key features of the data in terms of the coverage of expenditure items, payment channels, and the distribution of expenditures across regions and time. We highlight strengths and limitations of the data by comparing them to more consolidated lower-frequency information from external data sources. We find very similar expenditure patterns in Germany and Austria. We illustrate the advantages of the granular, higher-frequency information across expenditure items and locations by analyzing how consumption expenditures evolved during the COVID-19 crisis and beyond.
Keywords: C80; D12; E21; 330; consumption expenditures; transactional data; Austria; Germany; COVID-19